2021
DOI: 10.1590/0034-7167-2020-0122
|View full text |Cite
|
Sign up to set email alerts
|

Children with Congenital Zika Syndrome: the complexity of nursing care during hospitalization

Abstract: Objectives: to classify the degree of dependence on nursing care required by children with Congenital Zika Syndrome during hospitalization and to analyze their complexity. Methods: this is a descriptive, observational and quantitative study carried out in a pediatric ward of a public hospital in Rio de Janeiro. Data were collected from hospitalization records between June 2017 and April 2018. Results: 54% of the population studied showed a degree of dependence equivalent to semi-intensive care. On 37.5% of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a study of 145 children with CZS followed at a referral centre in Pernambuco [ 29 ], 49% had been hospitalised by age 24 months, with an average stay of 4 days and very similar discharge diagnoses as reported here. A smaller study from Rio de Janeiro reported gastrointestinal tract-related admissions as the main reason for hospitalisations, but with respiratory and nervous system problems as the next most important; this study also examined the nursing care required for the 41 hospitalisations studied, finding that 8% required intensive and 54% semi-intensive care (i.e., clinically unstable) [ 30 ]. The high risk of infections may partly reflect increased risk of broncho-aspirations in this population, where a high proportion may have persistent dysphagia, as well as infections associated with invasive devices.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 145 children with CZS followed at a referral centre in Pernambuco [ 29 ], 49% had been hospitalised by age 24 months, with an average stay of 4 days and very similar discharge diagnoses as reported here. A smaller study from Rio de Janeiro reported gastrointestinal tract-related admissions as the main reason for hospitalisations, but with respiratory and nervous system problems as the next most important; this study also examined the nursing care required for the 41 hospitalisations studied, finding that 8% required intensive and 54% semi-intensive care (i.e., clinically unstable) [ 30 ]. The high risk of infections may partly reflect increased risk of broncho-aspirations in this population, where a high proportion may have persistent dysphagia, as well as infections associated with invasive devices.…”
Section: Discussionmentioning
confidence: 99%